New Understanding and Improvement in Sintering Behavior of Cerium-Rich Perovskite-Type Protonic Electrolytes - Wang, Z.; Luo, Z.; Xu, Hengyue; Zhu, T.; Guan, D.; Lin, Z.; Chan, T.S.; Huang, Y.C.; Hu, Z.; Jiang, San Ping; Shao, Zongping (2024)
Protonic ceramic cells show great promises for electrochemical energy conversion and storage, while one of the key challenges lies in fabricating dense electrolytes. Generally, the poor sinterability of most protonic ceramic electrolytes, such as BaZr0.1Ce0.7Y0.1Yb0.1O3-δ, is attributed to the Ba evaporation at high temperatures. In a systematic and comparative study of BaCeO3 and BaZrO3, the results demonstrated that Ba tends to segregate to grain boundaries rather than evaporate. Additionally, thermal reduction of Ce4+ to Ce3+ promotes the displacement of Ce to the Ba-site or the exsolution of CeO2 phase, leading to an abnormal lattice shrinkage of perovskite phase and hindering the electrolyte densification. Contrary to previous beliefs that Ba deficiency inhibits the electrolyte sintering, the findings indicate that it surprisingly promotes the sintering of BaZrO3 perovskites, while excess Ba negatively affects its sintering behavior due to the accumulation of Ba species at grain boundaries. As to BaCeO3, excess Ba improves electrolyte sintering by suppressing the Ce exsolution at high temperatures. Meanwhile, Co-doping Zr and Ce in the B-site of protonic perovskite can optimize the sintering characteristic. These findings offer new insights into sintering of protonic perovskites and provide guidance for the development of new protonic devices.